Penicillium simplicissimum NL-Z1 Induced an Imposed Effect to Promote the Leguminous Plant Growth - Zhuang, Jiayao; Liu, Chao; Wang, Xiaoxue; Xu, Tongxin; Yang, Hao (Frontiers in Microbiology, 2021)
It is found effective for phytoremediation of the guest soil spraying method by adding microbes to promote the growth of arbor leguminous plant on a high and steep rock slope. However, its underlying mechanisms remain elusive. Here, some experiments were conducted to explore the multifunctions of Penicillium simplicissimum NL-Z1 on rock weathering, nodule growth, and beneficial microbial regulation. The results show that P. simplicissimum NL-Z1 significantly increased the release of phosphorus, potassium, calcium, and magnesium from the rock by 226, 29, 24, and 95%, respectively, compared with that of the control. A significant increase of 153% in Indigofera pseudotinctoria Matsum nodule biomass, accompanied by an increase of 37% in the leguminous plant biomass was observed in the P. simplicissimum NL-Z1 treatment than in the control treatment. Interestingly, even though P. simplicissimum NL-Z1 itself became a minor microbial community in the soil, it induced a significant increase in Mortierella, which, as a beneficial microbe, can promote phosphate-solubilizing and plant growth. The results suggest that P. simplicissimum NL-Z1 could induce an imposed effect to promote leguminous plant growth, which may be conducive to the development of the phytoremediation technique for high and steep rock slope. The study provides a novel thought of using the indirect effect of microbes, i.e., promoting other beneficial microbes, to improve soil environment.